Influence Profitability, Leverage, Company Size Towards Corporate Social Responsibility Disclosure (Empirical Study on Food and Beverage Sector and Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) for The 2016-2018 Period - Takiah, Fitriatul; Yuliusman, Yuliusman; Yuliana, Yuliana (Faculty of Economics and Business Universitas Jambi, 2024)
This study aims to determine the effect of profitability, leverage and company size variables on corporate social responsibility disclosure in food and beverage companies listed on the IDX in 2016-2018. The population of this study was food and beverage companies listed on the IDX in 2016-2018. The sampling technique used purposive sampling. There were 12 companies that met the criteria as samples. The software used for data processing was SPSS version 25. The results of this study are profitability affects corporate social responsibility disclosure, leverage affects corporate social responsibility disclosure, and company size affects corporate social responsibility disclosure. This study contributes to the importance of maintaining solid profitability, prudent leverage, and sufficient scale to enhance transparency in CSR reporting. Specifically, firms in the food and beverage industry should actively monitor these financial metrics to improve their CSR profile, which can attract socially conscious investors and reinforce stakeholder trust.